DOI: 10.11606/t.85.2019.tde-20052019-085251
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da radiação ionizante nas fases do ciclo evolutivo de >i<Aedes aegypti>/i< L. visando o seu controle através da técnica do inseto estéril

Abstract: AGRADECIMENTOS A Deus que permitiu que tudo isso acontecesse, sempre me concedendo saúde, paz, proteção e me ajudando nas horas mais difíceis, não somente na vida universitária, mas em todos os momentos de minha existência. Ao Prof. Dr. Valter Arthur, meu estimado orientador, por estar sempre disponível para solução de dúvidas e problemas que surgiram durante o desenvolvimento do projeto, além da grande amizade construída durante todos esses anos. Aos meus pais José Aparecido Machi e Maria Bernadete da Silva M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…These results when compared with other authors in the study of larva mortality showed that older larvae are more resistant the radiation. However, is necessary take into account the conditions of the fruit (water content, texture, stage of maturation) can be an important factor in relation to those caused effects on larval development of insects [26,27,28]. This can also be directly related the radiation doses required to eliminate the larvae of several varieties of fruits.…”
Section: Resultsmentioning
confidence: 99%
“…These results when compared with other authors in the study of larva mortality showed that older larvae are more resistant the radiation. However, is necessary take into account the conditions of the fruit (water content, texture, stage of maturation) can be an important factor in relation to those caused effects on larval development of insects [26,27,28]. This can also be directly related the radiation doses required to eliminate the larvae of several varieties of fruits.…”
Section: Resultsmentioning
confidence: 99%